2021
DOI: 10.1136/gutjnl-2021-324471
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and colonoscopy experience: lessons from two randomised trials

Abstract: Background and aimsArtificial intelligence has been shown to increase adenoma detection rate (ADR) as the main surrogate outcome parameter of colonoscopy quality. To which extent this effect may be related to physician experience is not known. We performed a randomised trial with colonoscopists in their qualification period (AID-2) and compared these data with a previously published randomised trial in expert endoscopists (AID-1).MethodsIn this prospective, randomised controlled non-inferiority trial (AID-2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
126
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 35 publications
3
126
0
1
Order By: Relevance
“…CADe seems to be effective in increasing adenoma detection regardless of the endoscopist's expertise, confirming a previous observation comparing experts and non-expert endoscopists [11].…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 1 more Smart Citation
“…CADe seems to be effective in increasing adenoma detection regardless of the endoscopist's expertise, confirming a previous observation comparing experts and non-expert endoscopists [11].…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…The main distinctive feature of our study is represented by the study setting. Although recent randomized trials have demonstrated the effectiveness of CADe systems in patients undergoing colonoscopy for mixed indications 8 24 , data in FIT + patients are limited by underpowered subgroup analyses 7 11 . The population-based organized FIT-based CRC screening program is a unique setting as the population included has a high prevalence of precancerous lesions and endoscopists’ participation in the screening program is dependent on a high ADR, which is continuously monitored and audited.…”
Section: Discussionmentioning
confidence: 99%
“…
We read the study conducted by Zippelius et al [1] with great interest and thank the authors for revealing a comparable noninferior performance between an artificial intelligence (AI) system and endoscopists. Although the test in a hospital independent of the system development provides validation evidence, unlike other high-quality trials with larger sample sizes and different clinic levels, this research did not detect different performance [2][3][4][5]. To maximize the confidence of the comparison, we would like to get a closer look at the study and make some comments.
…”
mentioning
confidence: 94%
“…Artificial intelligence (AI) is a disruptive technology, especially in medical image analysis [ 1 , 2 ]. AI is already assisting physicians in various clinical tasks and has shown promising results especially in digestive endoscopy [ 3 , 4 , 5 ]. To support and promote this technological innovation, the European Society of Gastrointestinal Endoscopy (ESGE) “suggests the possible incorporation of computer-aided diagnosis (CADx) to colonoscopy” [ 6 ].…”
Section: Introductionmentioning
confidence: 99%